Measles virus-induced immune suppression in the cotton rat (Sigmodon hispidus) model depends on viral glycoproteins - Niewiesk, S; Eisenhuth, I; Fooks, A; Clegg, J C; Schnorr, J J; Schneider-Schaulies, S; ter Meulen, V (Journal of virology, 1997)
Immune suppression during measles accounts for most of the morbidity and mortality associated with the virus infection. Experimental study of this phenomenon has been hampered by the lack of a suitable animal model. We have used the cotton rat to demonstrate that mitogen-induced proliferation of spleen cells from measles virus-infected animals is impaired. Proliferation inhibition is seen in all lymphocyte subsets and is not dependent on viral replication. Cells which express the viral glycoproteins (hemagglutinin and fusion protein) transiently by transfection induce proliferation inhibition after intraperitoneal inoculation, whereas application of a recombinant measles virus in which measles virus glycoproteins are replaced with the vesicular stomatitis virus G protein does not have an antiproliferative effect. Therefore, in vivo expression of measles virus glycoproteins is sufficient and necessary to induce inhibition of lymphocyte proliferation.